[Afisz. Incipit:] Terminarz pracy Ośrodka Metodycznego przy DOSZ w Gdańsku na kwiecień 1955 r. (Gdańsk : [wydawca nieznany], 1955)
Afisz z tabelą zajęć.
Keywords: 1901-2000; 1945-1989; Szkoły; Gdańsk (woj. pomorskie); Druki ulotne